WORKSHOP RPL KONSELING INDIVIDUAL BERBASIS POP BK SMP/MTs - Ali Rachman; Muhammad Andri Setiawan; Anita Anita (Universitas Muhammadiyah Pringsewu, 2018)
Workshop on the implementation of POP BK SMP/MTs-based individual counseling services held by MGBK SMP-Banjarbaru City were held with the intention of providing an understanding of the plan for implementing individual counseling services, so that counselor can use the individual counseling service plan properly. This workshop was carried out by presenting the material for the implementation of the service plan and then continued with the simulation of the case study-based manufacture, participants amounted to 38 people. The workshop implementation showed that counselors needed an in-depth understanding to use the plan for implementing individual counseling services as a counselee's initial information.